Do Firms Strategically Disseminate? Evidence from Corporate Use of Social Media - Jung, Michael J.; Naughton, James P.; Tahoun, Ahmed; Wang, Clare (The Accounting Review, 2018)
ABSTRACT We examine whether firms use social media to strategically disseminate financial information. Analyzing S&P 1500 firms' use of Twitter to disseminate quarterly earnings announcements, we find that firms are less likely to disseminate when the news is bad and when the magnitude of the bad news is worse, consistent with strategic behavior. Furthermore, firms tend to send fewer earnings announcement tweets and “rehash” tweets when the news is bad. Cross-sectional analyses suggest that incentives for strategic dissemination are higher for firms with a lower level of investor sophistication and firms with a larger social media audience. We also find that strategic dissemination behavior is detectable in high litigation risk firms, but not low litigation risk firms. Finally, we find that the tweeting of bad news and the subsequent retweeting of that news by a firm's followers are associated with more negative news articles written about the firm by the traditional media, highlighting a potential downside to Twitter dissemination. JEL Classifications: G14; G38; M10; M21; M41.